Hyperhomocysteinemia and intracranial aneurysm: A mendelian randomization study - Ma, Chencheng; Zhang, Weiwei; Mao, Lei; Zhang, Guangjian; Shen, Yuqi; Chang, Hanxiao; Xu, Xiupeng; Li, Zheng; Lu, Hua (Frontiers in Neurology, 2022)
Objective To investigate the link between genetic variants associated with plasma homocysteine levels and risk of intracranial aneurysm (IA) using two-sample Mendelian randomization. Methods We used single-nucleotide polymorphisms associated with human plasma homocysteine levels as instrumental variables for the primary analysis in a genome-wide association study of 44,147 subjects of European ancestry. Summary-level statistics were obtained for 79,429 individuals, including 7,495 IA cases and 71,934 controls. To enhance validity, five different Mendelian randomization methods (MR-Egger, weighted median, inverse variance weighted, simple mode, and weighted mode) were used for the analyses. Results The inverse variance weighted analysis method produced P-values of 0.398 for aneurysmal subarachnoid hemorrhage [odds ratio (OR): 1.104; 95% confidence interval (CI): 0.878–1.387], 0.246 for IA (OR: 1.124; 95% CI: 0.923–1.368), and 0.644 for unruptured IA (OR: 1.126; 95% CI: 0.682–1.858). The MR-Egger analysis showed no association between IAs and homocysteine, with all P > 0.05. Conclusion Using gene-related instrumental variables, the Mendelian randomization analyses demonstrated a lack of an association between plasma homocysteine levels and IAs or aneurysmal subarachnoid hemorrhage.